PERANCANGAN SISTEM APLIKASI PERMOHONAN PENGESAHAN PERTELAAN KANTOR WILAYAH BPN PROVINSI DKI JAKARTA - Irman Gantira; Niki Ratama (Informatika: Jurnal Teknik Informatika dan Multimedia, 2025)
Application Approval of Apartment Unit Land Titles application system is a system designed for the Regional Office of the National Land Agency of the Special Capital Region of Jakarta and the Provincial Government of the Special Capital Region of Jakarta as a form of collaboration in managing and approving apartment unit land titles, where this application is made web-based using a MySQL database. As a government agency tasked with serving the community, ease and efficiency of service time are important factors in serving the community. In designing the application system for application validation, the Rapid Application Development (RAD) method is used because this method is able to meet the needs for rapid application development that focuses on quality and meets the needs of the end user.